2023
DOI: 10.1001/jama.2022.24100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluvoxamine vs Placebo on Time to Sustained Recovery in Outpatients With Mild to Moderate COVID-19

Abstract: ImportanceThe effectiveness of fluvoxamine to shorten symptom duration or prevent hospitalization among outpatients with mild to moderate symptomatic COVID-19 is unclear.ObjectiveTo evaluate the efficacy of low-dose fluvoxamine (50 mg twice daily) for 10 days compared with placebo for the treatment of mild to moderate COVID-19 in the US.Design, Setting, and ParticipantsThe ongoing Accelerating COVID-19 Therapeutic Interventions and Vaccines (ACTIV-6) platform randomized clinical trial was designed to test repu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 17 publications
0
50
0
Order By: Relevance
“…Some limitations must be acknowledged such as the monocentric setting of the study, the open-label, retrospective, observational design, with a partial consideration of confounding variables that might concomitantly affect the inflammatory status and depressive psychopathology, and the lack of a control group (either placebo or other antidepressants). Indeed, the antidepressant fluvoxamine, which preliminarily proved to be efficacious in managing SARS-CoV-2 infection outcomes ( Boretti, 2022 ), turned out to show no significant effects in a subsequent placebo-controlled randomized clinical trial ( McCarthy et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some limitations must be acknowledged such as the monocentric setting of the study, the open-label, retrospective, observational design, with a partial consideration of confounding variables that might concomitantly affect the inflammatory status and depressive psychopathology, and the lack of a control group (either placebo or other antidepressants). Indeed, the antidepressant fluvoxamine, which preliminarily proved to be efficacious in managing SARS-CoV-2 infection outcomes ( Boretti, 2022 ), turned out to show no significant effects in a subsequent placebo-controlled randomized clinical trial ( McCarthy et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, fluvoxamine (100 mg twice daily) or placebo was administered as tolerated until day 15 This study was terminated early for futility No benefit Reis et al (2022) [ 66 ] TOGETHER Brazil High-risk symptomatic unvaccinated patients with COVID-19 Fluvoxamine (100 mg twice daily) (n = 741) and placebo (n = 756) for 10 days Fluvoxamine group showed significantly lower proportion of emergency setting for more than 6 h or transferred to tertiary hospital due to COVID-19 compared with placebo group Benefit Seo et al (2022) [ 70 ] Korea Patients with mild or moderate COVID-19 who were admitted to the community treatment centers Fluvoxamine (50 mg) (n = 26) or placebo (n = 26) was administered on day 1. Then, fluvoxamine (100 mg twice daily for about 10 days) or placebo was administered for tolerance until discharge from the community treatment centers A single-blind trial showed that there was no significant differences in clinical deterioration between the fluvoxamine group and placebo group No benefit Bramante et al (2022) [ 71 ] COVID-OUT USA Patients with COVID-19 Fluvoxamine (50 mg twice daily) (n = 334) and placebo (n = 327) for 14 days Fluvoxamine did not prevent the primary events such as hypoxemia, an emergency department visit, hospitalization, or death associated with COVID-19 No benefit McCarthy et al (2023) [ 72 ] ACTIV-6 USA Outpatients with mild to moderate COVID-19 Fluvoxamine (50 mg twice daily) (n = 674) and placebo (n = 614) for 10 days The median time to sustained recovery was 12 days in the fluvoxamine group and 13 days in the placebo group. There was no significant difference between the two groups No benefit …”
Section: Effects Of Fluvoxamine On Covid-19 Patientsmentioning
confidence: 99%
“…In 2023, McCarthy et al [ 72 ] reported the results of the Accelerating COVID-19 Therapeutic Interventions and Vaccines (ACTIV-6) platform randomized clinical trial (Table 2 ). Outpatients with mild to moderate COVID-19 (n = 1288) were randomly assigned to the fluvoxamine group (50 mg twice daily for 10 days; n = 674) and the placebo group (n = 614).…”
Section: Effects Of Fluvoxamine On Covid-19 Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trials of some drugs suggest possible benefit by reducing emergency department (ED) visits or hospitalizations, including fluvoxamine dosed at 100 mg twice daily and immediate-release metformin . Others have failed to show a reduction in ED visits or hospitalizations, such as fluvoxamine 50 mg twice daily . Although recently completed trials benefit from the increasing representation of vaccinated people, which is more relevant to the pandemic’s current state, the results have not affected treatment guidelines largely due to study design limitations, including definitions of outcomes that were of unclear significance in the US health care setting …”
Section: Introductionmentioning
confidence: 99%